Shoot regeneration from cotyledon nodes and production of anthraquinones from cell suspension culture of gelenggang (Cassia alata linn.) - Jaapar, Siti Safura (2015)
Great demands for plant resources to produce conventional drugs as well as traditional medicine due to their precious bioactive compounds have caused drastic depletion on natural biodiversity including Cassia alata L., especially in Malaysia. Plant tissue culture technology has become an option to reproduce the resources of preferred compounds, yet there is a gap of information on the species on in vitro cultures. Therefore through this study, the effect of plant growth regulators on seed germination and shoot regeneration using cotyledon nodes of C. alata had been determined. Besides, the effect of plant growth regulators on leaf-derived callus induction of the species and methyl jasmonate (MeJA) elicitation effect on cells growth in liquid medium, as well as on anthraquinones production also had been studied. The detection of anthraquinones was carried out using TLC and HPLC. The results showed that BAP at a concentration of 1 mg/L in MS medium gave excellent response in seed germination (77.33%) and MS medium supplemented 1 mg/L BAP and 1.5 mg/L NAA induced the highest number of shoots (2.07 ± 0.54 shoots per explants) with the mean length of 1.3 ± 0.1 cm from cotyledon node of the species. The maximum percentage (33.33%) of leaf derived callus has been obtained in MS medium added with 1 mg/L picloram. Meanwhile MS medium with 1 mg/L picloram and 0.2 mg/L BAP induced the highest percentage (100%) of creamy yellow, globular and friable callus with the highest dried weight (0.8 ± 0.03 g) after 50 days of cultures. Elicitation in suspension culture of MS + 1 mg/L picloram + 0.2 mg/L BAP treated with 0.1 μM MeJA stimulated the highest cells biomass production as 4.46 ± 0.49 grams of dried weight. Through TLC analysis, the retention factor (Rf) values of four anthraquinones were determined; rhein (Rf = 0.85), aloe-emodin (Rf =0.82), chrysophanol (Rf = 0.79) and physcion (Rf = 0.71). Physcion and rhein spots were detected from the crude extract from suspension culture treated with 1.0 μM MeJA. Single spot of aloe-emodin was presented from the crude extract from suspension culture treated with 0.1 μM MeJA. Meanwhile aloe-emodin and physcion spots were detected from the crude extract from suspension culture treated with 0.01 μM MeJA and without any elicitor treatment respectively. Chrysophanol was only detected in the leaf crude extract. Results from HPLC analysis showed that the highest concentration of aloe-emodin (2.63 ± 0.03 mg/g DW) occurred in the sample extract from cell suspension culture supplied with MS + 1 mg/L picloram + 0.2 mg/L BAP + 0.01 μM MeJA for 10 days culture. Besides, the highest concentration of rhein (4.53 ± 0.10 mg/g DW) was detected in the sample extract from cell suspension cultured in MS + 1 mg/L picloram + 0.2 mg/L BAP + 1 μM MeJA for 10 days culture. There was no chrysophanol detected in every sample extract except from leaf extract. It showed that the MeJA concentration and long duration of elicitation did affect the biomass of the cells, as well as the accumulation of anthraquinones in C. alata L. suspension cultures. As the conclusion, the shoot regeneration capability of cotyledon nodes of C. alata was determined, the cell suspension culture of this species was established and anthraquinones was produced via MeJA elicitation in cell suspension culture.